"The Refugee Crisis: British and Canadian Responses" : International Symposium Report - Lanphier, C. Michael; Spencer-Nimmons, Noreen (Refuge: Canada's Journal on Refugees, 1989)
January 4-7, 1989 marked the third international symposium to be co-sponsored by the Refugee Studies Programme at the University of Oxford, and the Centre for Refugee Studies (formerly the Refugee Documentation Project) at York University, Canada. The symposium title reflects the framework for British participants to address current refugees issues from the perspective of Britain's Race Relations Act, and Canadians from the perspective of the recent Multicultural Act.